Knowledge and Determinants of Use of Health Supplements among Undergraduates in Ipoh, Perak Malaysia - Sook Ching Chan (Journal of Global Pharma Technology, 2019)
Background Objectives: Research on health supplement usage among Malaysian undergraduate students is still limited although an average of USD17.30 was reported spent for nutritional supplements monthly.This study aimed to determine the usage of health supplements among the undergraduate students in Ipoh, Perak, Malaysia and the relationship between consumption and knowledge of health supplement among these students. Methods: This cross-sectional study was conducted in March to April 2018. Health sciences students and non-health sciences students from four different universities/colleges were selected through cluster sampling and random sampling method. A questionnaire that included socio-demographic data, lifestyle practices, usage of health supplement and assessment of knowledge of health supplements was given to selected students. Data analysis was done using SPSS 22.0 (Trial Version).Results: There were 374 respondents of which 79 students (21%) consumed health supplements. The majority of those who consumed health supplements (82%) were from Health Sciences, female (61%), overweight (44%) and with family income of more than RM5000 (39%). The top three most common reasons for using health supplements were “to maintain good health” (82.3%), “to ensure adequate nutrition” (54.4%) and “to improve immune function” (40.5%). The most common types of health supplements used were vitamins (44%) and minerals (23%). Fifty seven percent of the consumers had good knowledge compared to 30.5% of non - consumers. Conclusion: The majority of the consumers were from Health Sciences, female, overweight, had family income more than RM5000 and had better knowledge regarding the health supplements as compared to the non-consumers.Keywords: Health supplements, Undergraduates, Knowledge, Use.